The Islamic Republics of Central Asia and their importance in the American political perception. - Dawoud Ghazel, Assistant Professor Dr. Salam (The college of law and political science journal, 2023)
The Central Asian republics, after the collapse of the Soviet Union, becameimportant for the geopolitical position because of its importance to the internationaland regional balance and the total of the nine countries from the largest countriesin the world. As for maritime trade, it is also considered of great importance. As forthe natural wealth, it is added to the balance of the Central Asian republics. Fromthe foregoing, it seems clear in the nature of The geopolitical and demographicsof Central Asia in addition to the fact that they are Islamic countries due to theirdistinguished geographical location, especially as they are judged by a major andregional power that is active in the international arena (Russia, China, Turkey andIran, which makes the Central Asian region an area of competition and struggleto control the transportation and trade routes in Eurasia and shows the north ofWest and Southeast Asia, in addition to the huge reserves of oil, natural gas andminerals that this region possesses, make it under the second largest reserves ofthe world’s countries of these resources. Therefore, this region represented a greatLPSRUWDQFHLQWKH$PHULFDQSROLWLFDOSHUFHSWLRQLQOLJKWRIWKHLQWHQVLÀFDWLRQRIWKHFRQÁLFWZLWK5XVVLDDQG&KLQDDVZHOODV,UDQ